Cardiorespiratory Optimal Point in Professional Soccer Players: A Novel Submaximal Variable During Exercise - Silva,Christina Grüne de Souza e (2018)
Abstract Background: Maximal oxygen consumption (VO2max) and ventilatory threshold (VT) obtained during a cardiopulmonary exercise test (CPX) are used in the evaluation of athletes. However, the identification of these variables may sometimes be unreliable, which limits their use. In contrast, the cardiorespiratory optimal point (COP) is a submaximal variable derived from CPX with objective measurement and prognostic significance. However, its behavior in athletes is unknown. Objective: To describe the behavior of COP in professional soccer players and its association with VO2max and VT. Methods: VO2max, VT and COP were obtained retrospectively from 198 soccer players undergoing maximal treadmill CPX using ramp protocol. COP was defined as the lowest value of the ventilation/oxygen consumption ratio in a given minute of the CPX. The soccer players were stratified according to their field position: goalkeeper, center-defender, left/right-back, midfielder and forwarder. Continuous variables were compared using unpaired Student t test or ANOVA, or Mann-Whitney test or Kruskal-Wallis test depending on their distribution, and categorical variables were compared using chi-square test. Pearson correlation was used to test the association between COP and other ventilatory variables. A level of 5% was used for statistical significance. Results: COP (mean ± SD) was 18.2 ± 2.1 and was achieved at a speed 4.3 ± 1.4 km.h-1 lower than that achieved at the VT. While VO2max (62.1 ± 6.2 mL.kg-1.min-1) tended to be lower in goalkeepers (p < 0.05), the COP did not vary according to field position (p = 0.41). No significant association was observed between COP and VO2max (r = 0.032, p = 0.65) or between COP and VT (r = -0.003, p = 0.96). Conclusion: COP can be easily determined during submaximal exercise performed with incremental speed in soccer players and does not vary according to the athlete’s field position. The absence of association with VO2max and VT indicates that COP provides distinct and complementary information to these variables. Future studies are needed to determine the practical implications of COP in assessing athletes. (Int J Cardiovasc Sci. 2018; [online].ahead print, PP.0-0)